Quantifying preload alterations using a sensitive chest-mounted accelerometer. Issue 4 (29th December 2021) - Schmidt, S E; Kristensen, C B; Soerensen, K; Soegaard, P; Mogelvang, R
Abstract:  : Seismocardiography (SCG) is a technology where the chest wall vibrations from the beating heart are measured using a highly sensitive accelerometer. SCG offers continuous measurement of cardiac function and potential applications include remote monitoring, diagnostic assessments, prognostic health checks and biventricular pacemaker optimization. Aim: In the current study we examined how changes in preload influence SCG time intervals, by acute saline infusion. Methods: We included twenty-six subjects, sixteen subjects with cardiac disease such as hypertrophic cardiomyopathy, dilated cardiomyopathy, aortic valve disease or ischemic heart disease (age 45.8±17.7 years and 93% male) and ten subjects without known cardiac conditions (age 42.1±14.4 years and 70% male). SCG was recorded from the xiphoid process using a custom-made sensor before and after acute infusion saline (median 2.0 L). The SCG signals were sampled with 5000 samples per second in 60 seconds, the individual heartbeats were identified using a dedicated segmentation algorithm and an average SCG beat was computed and used for the data analysis. Using a recently proposed nomenclature the following SCG fiducial points was identified: Es which coinciding with mitral valve closure, Gs which to some degree coincides with aortic opening, Bd coinciding with aortic valve closure and Fd coinciding with mitral valve opening [1]. The Es-Gs time interval was used as a measure of isovolumetric contraction time (IVCT), the Gs-Bd time interval was used as an estimate of ejection time (ET) and the Bd-Fd time interval as an estimate of isovolumetric relaxation time (IVRT). Paired t-test was used to test for significant response after infusion, while a two sample t-test was used to test for a significant difference in the observed response in subjects with or with our cardiac disease. Results: For two subjects SCG after infusion was not obtained thus, twenty-four subjects were included in the final data analysis. In the whole group, acute saline infusion shortened the IVRT (Bd-Fd) from 91.0±15.3 ms to 82.7±15.3 ms (p=0.004) and prolonged the ET (Gs-Bd) from 329.4±35 ms to 343.4±33 ms (p<0.001). There was no significant change in IVCT (Es-Gs) which was 39.5±15.1 ms at baseline and 38.1±14.9 ms post-infusion (p=0.88). There was no significant difference in response between subjects with or without cardiac disease. Conclusion: Increase in preload shortened the SCG time intervals related to the isovolumetric relaxation period and prolonged the period related to ejection time. SCG time intervals capture changes in preload, which demonstrates that the SCG is a potential modality for quantification of cardiac dynamics. Funding Acknowledgement: Type of funding sources: None.